The Social Characteristics of Hungarian Historic City Centres - Szirmai, Viktória (Discussion Papers, 2012)
When taking a walk in Hungarian historic city centres today we don’t feel any more that something is badly missing in them and we are neither envious comparing Hungarian historic city centres with the European ones seeing them on trips, travelogues or as a locale of art films. Today local citizens running their errands in the city centre or Hungarian and foreign tourists sightseeing there all can find the same typical European and global style of built and social environment in Hungarian city centres like in any other cities of West-Europe. The newly built or renovated public and private buildings, the regenerated facades, public spaces, walking and shopping streets, elegant shops, restaurants, coffee houses and terraces busy in summer, the artistic and other products are all representing a kind of European style in a special local taste depending on city size, climate, cultural traditions and lifestyle. What char-acteristic features do social processes have in contemporary city centres (and cit¬ies) and what specific attributes do the social structure of city centres and the spa¬tial location of social problems and conflicts have? What social factors determine the transformation of Hungarian historic city centres? This paper is seeking an¬swers for these issues through a comparative analysis of the historic city centres of Hungarian cities, through the matching of Hungarian trends with West-Euro¬pean and East-Central European ones by presenting their most dominant mecha¬nisms. The objective of the basic and applied research carried out between 2004 and 2007 in Hungarian big cities and their urban areas is investigating the socio-spatial differences and social conflicts between the Hungarian urban areas and analysing the impacts of socio-economic problems on the social competitiveness of cities. Several methods have been used in the research. Beyond a representative survey of the local citizens, a document and a press analysis have been prepared and 100 interviews were made covering different profession groups. The project operated in a corporate form of consortium. The leader of consortium is the Sociological Research Institute of HAS.